Timestamp [videorecording (DVD)] - Bryhynets, Olha; Hukova, Valeriia; Kolomiiets, Mykola (Kimstim, 2026)
An intimate, time-woven portrait of young Ukrainians growing up amid change and uncertainty. Mixing diary footage, personal reflections, and quiet observation, Kateryna Gornostai's documentary captures a generation seeking meaning and continuity as their country transforms preserving fleeting moments of resilience, friendship, and becoming.